Culiacán-09: a new dual-purpose sorghum variety for the state of Sinaloa - López-Guzmán, Jesús Asunción; Moreno-Gallegos, Tomás; Melgoza-Villagómez, Claudia María; Hernández-Espinal, Luis Alberto (Revista Mexicana de Ciencias Agrícolas, 2025)
The new sorghum variety Culiacán-09 was developed in 2009 at the Valle de Culiacán Experimental Field-National Institute of Forestry, Agricultural, and Livestock Research and registered in the National Catalog of Plant Varieties of the National Seed Inspection and Certification Service with number SOG-651-130423 and breeder’s title 3156. This variety adapts to the sorghum-producing areas for the state of Sinaloa; it showed higher yields and is tolerant to the main pests and diseases that affect the crop in the region. Culiacán-09 is an amber-grained variety; it is recommended for irrigation and rainfed conditions; the average yield is 3.92 t ha-1 of grain and 29.6 t ha-1 of fresh forage. Culiacán-09 has better bromatological quality than commercial hybrids in forage, with 7% protein and 77% digestibility, it exceeded commercial hybrids by 26% and 31% on average, respectively. It is tolerant of diseases that are present in the region, such as ergot, anthracnose, panicle blight, and carbonaceous rot of the stem.